Bisphosphonates inhibit the growth of mesothelioma cells in vitro and in vivo - Wakchoure, Savita; Merrell, Melinda A; Aldrich, Wayne; Millender-Swain, Telisha; Harris, Kevin W; Triozzi, Pierre; Selander, Katri S (Clinical cancer research, 2006)
Bisphosphonates (such as risedronate and zoledronate) are widely used inhibitors of bone resorption. Despite their in vitro antiproliferative effects in various cancer cells, bisphosphonates have not exhibited significant antitumor efficacy in animal models of visceral cancer, which may be due to their poor bioavailability. The diagnostic use of radioactive bisphosphonates has revealed the accumulation of bisphosphonates in mesothelioma, which prompted us to test the antitumor efficacy of bisphosphonates in this disease. Treatment with either risedronate or zoledronate (2 x 10(-4) to 2 x 10(-6) mol/L) inhibited the growth of AB12 and AC29 mouse mesothelioma cells and induced the accumulation of unprenylated Rap1A in these cells. Both these in vitro effects were reversed by geranygeraniol, an end product of the mevalonate pathway that these bisphosphonates inhibit. Both bisphosphonates also induced the phosphorylation of the p38 mitogen-activated protein kinase in AB12 and AC29 cells. The inhibition of p38 augmented bisphosphonate-induced growth inhibition in these cells. Bisphosphonate-induced p38 phosphorylation was not reversible by geranylgeraniol. Risedronate (15 mg/kg) and zoledronate (0.5 mg/kg) inhibited the growth of s.c. tumors and increased the median survival of mice with i.p. mesothelioma tumors in vivo. In conclusion, risedronate and zoledronate inhibit the mevalonate pathway and induce p38 activation in mesothelioma cells in vitro. The effects on the mevalonate pathway dominate because the net result is growth inhibition. Both bisphosphonates also inhibit mesothelioma tumor growth in vivo and prolong the survival of mesothelioma-bearing mice. These results support further study of bisphosphonates in the management of mesothelioma.